DOI: 10.3990/1.9789036544061
|View full text |Cite
|
Sign up to set email alerts
|

Energy-efficient Medium Access Control for Transmit Reference Modulation

Abstract: Acronyms 202 • Military applications: Low power, robust WSNs are very much suitable for military applications because of their capability to work in a harsh environment. WSNs can help the military to monitor their allies and enemies, collect information, perform surveillance of battlefield, detection of chemical, biological, nuclear weapons, etc. [1]. • Commercial applications: Many commercial applications rely on WSNs for i) Research question 1: How can the features of transmit reference modulation be exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(164 reference statements)
0
3
0
Order By: Relevance
“…Using the definition of variance from (23), the noise contribution Ψ yy is written as The second term in the integrand can be solved similarly as in (19). Using the definition of z yy (t) from (14a), the first term in the integrand can be written as…”
Section: A Signal Self-mixing Productmentioning
confidence: 99%
“…Using the definition of variance from (23), the noise contribution Ψ yy is written as The second term in the integrand can be solved similarly as in (19). Using the definition of z yy (t) from (14a), the first term in the integrand can be written as…”
Section: A Signal Self-mixing Productmentioning
confidence: 99%
“…Therefore, it is pertinent to avoid many simultaneous links in a given time slot. In this context, valuable contributions were made in the medium access control (MAC) track of the WALNUT project [72], which we summarize in this section. Medium access control (MAC) is at the heart of every communication network.…”
Section: Ma and Channel Access Protocolsmentioning
confidence: 99%
“…It was found that the expected throughput increases with the pool size of the usable frequency offsets. With a sizable the pool (∼25) of usable frequency offsets, more than 100 links can be established in a certain time-frame [72,Sec. 5.4].…”
Section: Ma and Channel Access Protocolsmentioning
confidence: 99%